2019
DOI: 10.12944/cwe.14.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Waste Management at Construction Sites in the Municipality of Manaus, Amazonas, Brazil: Characterization of the Current Situation

Abstract: This research aimed the characterization of the current production of construction waste in the city of Manaus, Amazonas, Brazil, and its impacts on the environment of the Amazon Region. The significance of this research work is to contribute to the improvement of the environmental management of waste in the construction sites of the city of Manaus, with the aim of preserving the Amazonian environment. This research also sought to characterize the existing problems in the environmental management of constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…In the municipality of Manaus, the only available legal solution for CDW disposal is the municipal land ll. However, high deposition costs are applied, and therefore construction companies tend to outsource the transport and disposal of their CDW to private companies operating in this area (Oliveira et al 2019a).…”
Section: Analysis Of the Current Practices For Cdw Management In Manausmentioning
confidence: 99%
See 2 more Smart Citations
“…In the municipality of Manaus, the only available legal solution for CDW disposal is the municipal land ll. However, high deposition costs are applied, and therefore construction companies tend to outsource the transport and disposal of their CDW to private companies operating in this area (Oliveira et al 2019a).…”
Section: Analysis Of the Current Practices For Cdw Management In Manausmentioning
confidence: 99%
“…These construction companies refer very high costs with CDW management -only metal waste is sold for recycling purposes, and the transport and disposal of other produced waste is outsourced to private companies. Wood and paper/cardboard waste, produced in high quantities in these industries and having high reuse and recycling potential, are not being valorised due to the lack of an organized system for waste commercialization (Oliveira et al 2019a).…”
Section: Analysis Of the Current Practices For Cdw Management In Manausmentioning
confidence: 99%
See 1 more Smart Citation
“…In the search for cheaper solutions, it was decided in this research to study the addition of Ca(OH)2 to the pervious concrete during the preparation, because the high porosity of this material facilitates the penetration of external gases of the atmosphere, which catalyze the carbonation in the process for the CO2 sequestration, as the pH within the internal structure (De Oliveira, 2018). Studies for adsorption of CO2 by porous solid materials used techniques for CO2 capture technologies with CaO-based sorbent, applied for high-temperature (Jamrunroj et al, 2019), but it is also a process that uses a lot of energy and is very expensive.…”
Section: Introductionmentioning
confidence: 99%
“…These negative impacts are of major importance in sensitive natural environments, justifying the relevance of this research in the city of Manaus, in the central Amazon, Brazil. A previous study involved the quantification of CDW produced at 4 construction sites in the city of Manaus, and the costs involved in its management and disposal (Oliveira et al, 2019). The results showed that high quantities of wood and paper waste are produced, with considerable disposal costs, in spite of the high potential to recycle and re-use these types of waste.…”
Section: Introductionmentioning
confidence: 99%